Restoring elbow flexion with latissimus dorsi to biceps transfer in an incomplete brachial plexus injury: a case report - Meirizal, Meirizal; Irfantian, Ardicho; Mustofa, Fuad Dheni; Huwaidi, A Faiz; Lo, Agung Susilo (Published by Universitas Gadjah Mada, 2025)
A brachial plexus injury is a common injury to the peripheral nerves, which can impair upper arm motion and diminish the quality of life. A 19 y.o. male experienced weakness in his right upper extremity after undergoing an open reduction and internal fixation (ORIF) procedure for a distal third radius and ulnar fracture four mo before the visit. Electroneuromyography revealed a dysfunction of the C4-T1 nerves, particularly affecting motor functions such as elbow flexion. The patient underwent latissimus dorsi advancement to biceps transfer with satisfactory results. The latissimus dorsi transfer procedure involves detaching a portion of the latissimus dorsi muscle and rerouting it to attach to the area where the biceps tendon inserts into the forearm. This transferred muscle can then be used to regain elbow flexion function. The latissimus dorsi is a powerful muscle, and transferring it offers the potential for greater restored elbow flexion strength and range of motion.